Answer:
The simplified expression would be 4
Step-by-step explanation:
So since we have parentheses in this expression we have to use the steps of PEMDAS (parentheses, Exponent, Multiplication, Division, Addition, Subtraction)
So the first step is to solve what's in the parentheses [tex](4+10)=(14)\\(6+5)=(11)[/tex]
Then we multiply [tex]2(14)=28\\-3(11)=-33[/tex]
Since we have simplified the equation so far let's write it out
[tex]9+28-33[/tex]
Now we just solve the equation as written
[tex]9+28=37\\37-33=4[/tex]